Measuring Factors that Influence Decisions to Become a Veterinarian - Royal Kenneth D.; Regina Schoenfeld-Tacher Regina; Kedrowicz April A.; Hardie Elizabeth M.; Flammer Keven (Tabriz University of Medical Sciences, 2015)
Introduction: Veterinary medical education; Psychometrics; Career influence; The purpose of the present study was twofold. First, we sought to evaluate the psychometric properties of a newly developed instrument designed to measure factors incoming veterinary medical students indicated were important (or not) in their decision to become a veterinarian. Second, we sought to produce a measure of these factors by utilizing a state-of-the-art psychometric modeling technique to produce an empirical hierarchy that illustrates the construct of interest and make appropriate inferences about the findings. Methods:The Career Influence Factors Survey (CIFS) was administered to an incoming class of veterinary medical students. Data were analyzed via the Rasch Rating Scale Model. The psychometric properties of the instrument were evaluated according to Messick's framework of construct validity. Results: Results indicate the Career Influence Factors Survey is a psychometrically-sound instrument capable of accurately and reliably measuring veterinary medical students' motivations for becoming a veterinarian. Substantive results indicated issues pertaining to animal welfare were the most important in making the decision to become a veterinarian. Previous exposure to a particular animal or family pet was only moderately influential in students' decision to pursue a career in veterinary medicine. Factors such as a desire to work on food production issues and anticipated earning potential tend to be of lesser importance to incoming students. Conclusion: We encourage others to utilize the instrument and/or adopt the methodology to evaluate the psychometric properties of other instruments. Substantive findings generally corroborated findings from previous studies, but may identify new insights for improving the recruitment of veterinary medical students.